Avaliação da resistência do mamoeiro 'Aliança' a Meloidogyne incognita e M. javanica - Carrion, Paula Abiko Navarro (2023)
The papaya tree is very important for national fruit growing, especially for the regional economy, with Espírito Santo as the largest producer. The occurrence of nematodes in the crop has already been reported, however, their impacts on production have not yet been properly quantified. The objective of this work was to evaluate the resistance of Carica papaya L. 'Aliança' to the species Meloidogyne incognita and M. javanica and the development of plants under the effect of two types of fertilization before the reproduction of these pathogens. Two experiments were carried out in a greenhouse, the first in randomized blocks, with six treatments, two replications and a 3x2 factorial scheme, until the production phase. In the second, to evaluate seedlings, a completely randomized design was used, with three treatments and 14 replications. The vegetative growth of the plants was evaluated by periodic measurements of plant height, number of leaves, stem diameter and number of flowers and fruits (when present). At the end, the mass of shoots and fresh roots, root length (only in the second experiment), as well as the final population of nematodes in the root and soil and the reproduction factor for each species were measured. Analyzes of variance and Tukey's test at 5% were performed using the R software. Papaya 'Aliança', according to Oostenbrink's criteria, was considered susceptible in adulthood and resistant in seedlings. Despite being a host of these pathogens, at the population level obtained, the growth and production variables were not affected, indicating that 'Aliança' is tolerant to the presence of these nematodes. As for the fertilizers used, the one that contained seaweed extract in its composition proved to be effective in reducing the reproduction factor for the two studied species.